Increased Rubisco content in maize mitigates chilling stress and speeds recovery. Issue 6 (20th December 2019) - Salesse‐Smith, Coralie E.; Sharwood, Robert E.; Busch, Florian A.; Stern, David B.
Summary: Many C4 plants, including maize, perform poorly under chilling conditions. This phenomenon has been linked in part to decreased Rubisco abundance at lower temperatures. An exception to this is chilling‐tolerant Miscanthus, which is able to maintain Rubisco protein content under such conditions. The goal of this study was to investigate whether increasing Rubisco content in maize could improve performance during or following chilling stress. Here, we demonstrate that transgenic lines overexpressing Rubisco large and small subunits and the Rubisco assembly factor RAF1 (RAF1‐LSSS), which have increased Rubisco content and growth under control conditions, maintain increased Rubisco content and growth during chilling stress. RAF1‐LSSS plants exhibited 12% higher CO2 assimilation relative to nontransgenic controls under control growth conditions, and a 17% differential after 2 weeks of chilling stress, although assimilation rates of all genotypes were ~50% lower in chilling conditions. Chlorophyll fluorescence measurements showed RAF1‐LSSS and WT plants had similar rates of photochemical quenching during chilling, suggesting Rubisco may not be the primary limiting factor that leads to poor performance in maize under chilling conditions. In contrast, RAF1‐LSSS had improved photochemical quenching before and after chilling stress, suggesting that increased Rubisco may help plants recover faster from chilling conditions. Relatively increased leaf area, dry weight and plant height observed before chilling in RAF1‐LSSS were also maintained during chilling. Together, these results demonstrate that an increase in Rubisco content allows maize plants to better cope with chilling stress and also improves their subsequent recovery, yet additional modifications are required to engineer chilling tolerance in maize.